Comparison of Ethanol and Acetone Mixtures for Extraction of Condensed Tannin from Grape Skin - Downey, M.O.; Hanlin, R.L. (South African Journal of Enology and Viticulture, 2016)
Discrepancies in condensed tannin concentrations in grape skin determined by different analytical methods prompted the closer examination of aspects of the methodologies. One of these was the choice of extraction solvent. Condensed tannins were extracted from Shiraz grape skins using a range of aqueous solvent mixtures ranging from zero to 100% acetone and ethanol to examine the relative effectiveness of each solvent mixture and to determine whether different solvent mixtures extracted similar condensed tannin components. Acetone extracted more condensed tannin than ethanol. Mixtures of 50 to 70% acetone were equally effective. The most effective ethanol concentration was 50%. Epicatechin-gallate terminal subunits were not detected by HPLC following acid-catalysed cleavage in any of the extraction solvents. Extension subunit composition was similar between solvents across most mixtures. Polymers were generally shorter in the ethanol extracts than in the acetone extracts. Despite differences in tannin concentration and polymer length, the subunit composition was similar in 50% ethanol and 70% acetone. More tannin and tannins with longer polymer lengths were extracted with 70% acetone than with 50% ethanol. This suggests that all grape skin tannins are similar in composition, varying only in length. Thus, 50% ethanol and 70% acetone would give a fair indication of the grape skin tannin composition extracted into wine. However, both 50% ethanol and 70% acetone may overestimate the amount of tannin that is extracted into wine, as wine typically has a much lower solvent concentration, ranging between 10 and 15% ethanol.